The Effect of Altruism and Compassion on Employee Per-formance with Organizational Resilience as A Mediating Variable - Anggra Wahyuni; Zainnur M. Rusdi (International Forum of Researchers and Lecturers, 2026)
Particularly in light of the increasingly dynamic workplace, employee performance plays a critical role in promoting organizational sustainability and effectiveness. Altruism and compassion are examples of prosocial activities that are thought to increase employee performance and foster a healthy work environment. With organizational resilience acting as a mediating variable among educational staff at the University of Lampung's Faculty of Economics and Business, this study attempts to examine the impacts of compassion and altruism on worker performance. 69 employees of the University of Lampung's Faculty of Economics and Business participated in this quantitative study, which used a survey method. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the data. The findings show that employee performance is not much impacted by benevolence. Furthermore, the impact of altruism on worker performance cannot be mitigated by organizational resilience. Additionally, employee performance is not directly and significantly impacted by compassion. Nonetheless, it was discovered that the impact of compassion on worker performance was considerably mediated by organizational resilience. These results show that when a company is able to adapt, retain stability, and effectively respond to change, compassion can help improve employee performance. In the context of higher education institutions, this study advances the knowledge on prosocial behavior and organizational resilience. Practically speaking, the results emphasize how crucial it is to build organizational resilience and foster a positive workplace culture in order to sustainably raise employee performance.